Synthesis of Homopolymers and Copolymers Containing an Active Ester of Acrylic Acid by RAFT: Scaffolds for Controlling Polyvalent Ligand Display - Gujraty, Kunal V. (2008)
We describe the synthesis of activated homopolymers and copolymers of controlled molecular weight based on the controlled radical polymerization of N-acryloyloxysuccinimide (NAS) by reversible addition fragmentation chain transfer (RAFT). We synthesized activated homopolymers in a range of molecular weights with polydispersities between 1 and 1.2. The attachment of an inhibitory peptide to the activated polymer backbone yielded a potent controlled molecular weight polyvalent inhibitor of anthrax toxin. To provide greater control over the placement of the peptides along the polymer backbone, we also used a semi-batch copolymerization method to synthesize copolymers of NAS and acrylamide (AAm). This approach enabled the synthesis of copolymers with control over the placement of peptide-reactive NAS monomers along an inert backbone; subsequent functionalization of NAS with peptide yielded well-defined polyvalent anthrax toxin inhibitors that differed in their potencies. These strategies for controlling molecular weight, ligand density, and ligand placement will be broadly applicable for designing potent polyvalent inhibitors for a variety of pathogens and toxins, and for elucidating structure-activity relationships in these systems.